Real-time lane detection of autonomous vehicle - Sowinkumar Namel Nagarajan (2023)
This system is much efficient and convince for the user to be experianced on his entire life.Real-time images will be captured on every second to provide relevant information's and vehicle positions on the current lane. In past decades, accidents occurred due to visibility issues during raining season. Therefore, this system was initialized to provide a better experienced and safety environment for the user to move on.